Study of triamcinolone release and mucoadhesive properties of macroporous hybrid films for oral disease treatment - Oshiro, Joaõ Augusto [UNESP]; Nasser, Neima Jamil [UNESP]; Chiari-Andreó, Bruna Galdorfini [UNESP]; Cuberes, M Teresa; Chiavacci, Leila Aparecida [UNESP] (IOP Publishing, 2018)
The aim of this study was to develop macroporous mucoadhesive films from ureasil-polyether materials for future application in oral disease treatment. The films were prepared via the sol-gel route by using polyethylene oxide (PEO) and polypropylene oxide (PPO) polymers; triamcinolone was used as a model drug for in vitro release testing. The in vitro drug release assay revealed that Ureasil-PEO500 films containing 3% and 6% of the model drug released 56% and 33% of the initial mass, respectively. This difference in release is probably due to a higher amount of the drug, making relaxation of polymer chains difficult, causing reduced swelling. For Ureasil-PPO400 films the amount of the drug did not influence the release; the rate of release was 5.1% after 12 hours and this lower release can be explained by the hydrophobic character of Ureasil-PPO400 polymeric chains. These results are in agreement with the swelling results. The swollen behavior of the films was monitored by small-angle X-ray scattering measurements (SAXS). Atomic force microscopy demonstrated that all the films are macroporous (pores around 400 nm) but the Ureasil-PEO500 film possesses more pores than Ureasil-PPO400. Mucoadhesion force assessment revealed that all ureasil-polyether films with or without a model drug have higher mucoadhesion values than the commercial product. These results indicate that macroporous ureasil-polyether mucoadhesive films are promising candidates for oral disease treatment considering their cost, biocompatibility, drug release and ease of handling, and they have more adhesion force to oral mucosa than the commercial product.
Keywords: macroporous ureasil-polyether material; mucoadhesive film; oral disease treatment; triamcinolone